2017
DOI: 10.1139/gen-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in CIRCADIAN CLOCK ASSOCIATED 1 is associated with flowering time in Brassica rapa

Abstract: Flowering time is a very important agronomic trait and the development of molecular markers associated with this trait can facilitate crop breeding. CIRCADIAN CLOCK ASSOCIATED 1 (CCA1), a core oscillator component of circadian rhythms that affect metabolic pathways in plants, has been implicated in flowering time control in species of Brassica. CCA1 gene sequences from three Brassica rapa inbred lines, showing either early flowering or late flowering phenotypes, were analyzed and a high level of sequence varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In the Chinese cabbage and leafy varieties of Brassica rapa, early flowering generally leads to decreased productivity and yield. A recent study found that B. rapa cultivars with variable photoperiod sensitivities contained a great deal of sequence variation in the BrCCA1 homolog and several of these variations could be associated with a delayed flowering phenotype, suggesting that CCA1 is a good candidate for marker-assisted breeding in Brassica (Yi et al 2017). In tomato, deletion of the LNK2 homolog likely enabled cultivation of this crop beyond its natural range to higher latitudes, perhaps by lengthening the period of the circadian clock (Müller et al 2018).…”
Section: Other Clock Gene Variants Influencing Photoperiodic Flowerinmentioning
confidence: 99%
“…In the Chinese cabbage and leafy varieties of Brassica rapa, early flowering generally leads to decreased productivity and yield. A recent study found that B. rapa cultivars with variable photoperiod sensitivities contained a great deal of sequence variation in the BrCCA1 homolog and several of these variations could be associated with a delayed flowering phenotype, suggesting that CCA1 is a good candidate for marker-assisted breeding in Brassica (Yi et al 2017). In tomato, deletion of the LNK2 homolog likely enabled cultivation of this crop beyond its natural range to higher latitudes, perhaps by lengthening the period of the circadian clock (Müller et al 2018).…”
Section: Other Clock Gene Variants Influencing Photoperiodic Flowerinmentioning
confidence: 99%
“…Two types of CCA1 alleles were detected and related to freezing-tolerant cabbage traits. In another study, the natural variation in CCA1 was associated with the flowering time in B. rapa and a high level of sequence variation was identified [36]. Genetic mapping and analysis of families of heterogeneous inbred lines showed that the natural variation in GI is responsible for a major quantitative trait locus in the circadian period in B. rapa.…”
Section: Circadian Clock Network In Brassica Cropsmentioning
confidence: 96%